The four-dimensional human : ways of being in the digital world - Scott, Laurence (New York, NY : W. W. Norton & Company, 2016)
"Hailed as a 'New Generation Thinker" by the Arts and Humanities Research Council and the BBC, the author, blending tech-philosophy with a vast array of insights, shows how we are entering into a four-dimensional world, filled with ceaseless communication, instant information and global connection, that is dramatically changing us,"--NoveList
Introduction : The reverse peephole -- Anatomically correct -- A different kind of buzz -- Style after substance -- Keeping and killing time -- Weeping Toms -- The cabin in the woods -- The blank screen -- Epilogue : fairy fire
Revised edition of the author's The four-dimensional human, 2015
Includes bibliographical references (pages 237-246)
Keywords: Internet -- Social aspects; Digital media -- Social aspects; Human-computer interaction; Print books